Factors Influencing Profitability and Payment Regularity: A Study of Building and Facilities Maintenance Service Providers in Malaysia - Shiridharan, Ganesan Muthi (2019)
Micro and SME busines s is seen as backbone of a developing nation’s economy. As a nation is developing more infrastructure is built to accommodate this growth. This infrastructure and its facilities need to be maintained and serviced regularly. This research aspires to find th e factor effecting profitability and payment regularity of Micro and SME companies involved in building and facilities maintenance. The objective of this research is to determine the level of importance of factor a ffecting profitability and payment regular ity of building and facilities maintenance service provider. The literature review has narrowed the factors to main four which are p ayment, w orkforce, l ack of i nformation and u nethical. It is also revealed during literature review that most of research is done on large enterprises. It is also found that lot research and solution suggested is based on large enterprise. The research method chosen for study is explanatory method and the data is collected by distributing questionnaire to all the service provide r and contractor involved in this facility and building maintenance industry where the collected data is analysed using descriptive analysis and Relative Importance Index method. Total of 199 participant take part in the survey. The factors are ranked base respond received. It is found that Workforce is ranked first followed by Payment, Lack of information and Unethical. As recommendation, more research to be conducted on Micro contractors or service provider. Current research focused more on Payment issue while neglecting other matter hence variety of research and from other point of view is needed. The conclusion of research is the main factor effecting the profitability and payment regularity and their ranked as followed Workforce, Payment, Lack of inform ation and Unethical. Government shouldn’t burden these contractors with fees and make sure the policies and act are helpful and friendly to them.